Perbandingan permainanm tradisional dan permainan modern terhadap keterampilan fisik anak Sekolah Dasar - Syach Agung, Moammar Saddam; Rukmana, Anin; Dinangsit, Dinar (Jurnal Porkes, 2024)
This study shows that traditional games and modern games can improve children's physical skills. The purpose of this study is to determine whether or not there is an effect of the game on children's physical skills and which is more effective than the two games. Using a quantitative approach with a quasi experimental design. This study includes two groups, namely the traditional game group and the modern group. The sample in this study consisted of 36 students using random sampling technique. Traditional games have an average increase to 47.44 and modern to 39.94. In N-Gain there are 11 samples that have an increase in modern games there are 6 samples that have an increase. The paired sample T-Test analysis of traditional games obtained a significance of 0.000, and modern 0.005. In the normality test the traditional game has Sig. 0.67, modern has Sig 0.58 and the homogeneity of both has a result of 0.47. In the last analysis, the lower independent sample T-Test has a value of -.0864148 and upper -.0897481 and for Sig (2 tailed) it is 0.009. The results of the discussion show that there are differences in traditional modern games on children's physical skills.